"The state of mind tells me it's dirty": menstrual shame amongst women using a vaginal ring in Sub Saharan Africa. Issue 1 (2nd January 2020) - Duby, Zoe; Katz, Ariana; Musara, Petina; Nabukeera, Josephine; Zimba, Chifundo Colleta; Woeber, Kubashni; Palanee-Phillips, Thesla; van der Straten, Ariane
ABSTRACT: Socio-cultural beliefs and practices surrounding menses influence women's sexual and reproductive health behaviors and decision-making. We analyzed menstrual experiences within the context of the MTN-020/ASPIRE clinical trial during which women were asked to use a monthly vaginal ring for HIV prevention. The qualitative component of the trial was conducted during February 2013-June 2015, included interviews and focus group discussions with 214 women aged 18–42, in Malawi, Zimbabwe, Uganda, and South Africa. Emotions of shame, embarrassment and disgust relating to menses emerged. Menstruation was referred to using euphemistic terms or language about dirtiness. Women were uncomfortable touching their own menstrual blood when removing vaginal rings and felt embarrassed about study staff seeing blood on returned rings. Despite reassurances, women felt ashamed performing study procedures while menstruating, leading to missed study visits. Women's aversion to menstrual blood was linked to narratives about avoiding sex during menses and beliefs about its potential harms. Women associated men's disgust pertaining to menstrual blood with men's willingness to use condoms for sex only during menses, highlighting another way through which socio-cultural beliefs and practices around menstruation affect HIV protective behaviours. These findings provide novel insight into menstrual shame among women in these four countries.